2017
DOI: 10.1002/ejp.1088
|View full text |Cite
|
Sign up to set email alerts
|

Altered pain sensitivity and axioscapular muscle activity in neck pain patients compared with healthy controls

Abstract: Neck pain patients report increased symptoms following upper limb activities. This study shows that repeated arm movements caused differentiated responses in pain sensitivity and muscle activity between subgroups of neck pain patient and asymptomatic controls. Such findings may be of great clinical significance when planning rehabilitation for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 37 publications
5
41
2
1
Order By: Relevance
“…It is important to emphasize that not all chronic pain populations consistently demonstrate an impaired EIH response and different measures have been used to quantify EIH (eg, clinical pain intensity vs pressure pain threshold) that may influence both the underlying mechanism and observed response to exercise. Although limited to a few studies, impaired EIH has also been observed in painful diabetic neuropathy 66 and chronic neck pain, 18 whereas a normal EIH response has been observed in those with rheumatoid arthritis 37, 88 and chronic low back pain. 96 Furthermore, in contrast with the findings of Burrows et al, 15 Kosek et al 73 observed intact local and global EIH in individuals with end-stage hip and knee OA.…”
Section: Overview Of Eih In People With Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that not all chronic pain populations consistently demonstrate an impaired EIH response and different measures have been used to quantify EIH (eg, clinical pain intensity vs pressure pain threshold) that may influence both the underlying mechanism and observed response to exercise. Although limited to a few studies, impaired EIH has also been observed in painful diabetic neuropathy 66 and chronic neck pain, 18 whereas a normal EIH response has been observed in those with rheumatoid arthritis 37, 88 and chronic low back pain. 96 Furthermore, in contrast with the findings of Burrows et al, 15 Kosek et al 73 observed intact local and global EIH in individuals with end-stage hip and knee OA.…”
Section: Overview Of Eih In People With Chronic Painmentioning
confidence: 99%
“…96 Furthermore, in contrast with the findings of Burrows et al, 15 Kosek et al 73 observed intact local and global EIH in individuals with end-stage hip and knee OA. Impaired EIH has been observed after repeated shoulder movements in people with whiplash-associated disorder (WAD), 18 whereas a normal EIH response was seen after an isometric leg muscle contraction. 119 In contrast, impaired EIH is typically, 56,119,147 observed in patients with WAD after aerobic exercise, highlighting the variability of the EIH response in chronic pain populations and suggesting a possible difference in EIH according to the type of exercise and pain condition.…”
Section: Overview Of Eih In People With Chronic Painmentioning
confidence: 99%
“…Only two studies 8,43 classified patients into groups of different levels of pain and disability. Nine studies investigated patients with localized neck pain 7,8,11,12,36,56,72,78,81 , while ten studies investigated patients with concurrent pain in other body regions such as upper limbs 30,43,51,54,63,65,76,77,82,90 . The other studies did not describe if patients had concurrent pain.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Subjects with neck pain have less muscle strength and activity than healthy people [8,9]. Pain sensitivity and axioscapular muscle activity have altered in neck pain patients compared with healthy controls [10]. Researchers have shown a relationship between decreased muscle strength and endurance with chronic nonspecific neck pain [11].…”
Section: Introductionmentioning
confidence: 99%